The Development of a Competency-Based Curriculum on Social Entrepreneurs in the Elderly Care Business for Community Nurses - Panawatanakul, Suwimon; Rukkusal, Narinrat; Ramwarungkura, Anuchai (Journal of health and health management, 2022)
This research aimed to study the competence of social entrepreneurs in the elderly care business and to develop a competency-based curriculum for social entrepreneurship in the elderly care business for community nurses. The research was divided into 2 phases: Phase 1 was to study the competence of community nurses, as social entrepreneurs in the elderly care business. The results of this competency study were considered in a group discussion of 23 experts, selected through purposive sampling. Next, the results of the group discussion were analyzed. It was found that the competencies of social entrepreneurship in the elderly care business consisted of 4 competencies, namely: 1) entrepreneurial competency, 2) competence in developing social innovation, 3) social competency, and 4) professional health services competency. The index of item-objective congruence determined that the occupation, key purpose, key role, key function, units of competency, elements of competency, and performance criteria were highly consistent with a score of 1, except for items 35, 52, 74, and 76, which had an assessment result of 0.95. Phase 2 developed a competency-based curriculum on social entrepreneurship in the elderly care business for community nurses by converting these competencies of social entrepreneurship in the elderly care business for community nurses into four modules, namely: Module 1: Social Business Development consisting of fourteen learning outcomes of ninety training hours. Module 2: the Development of Social Innovation and Module 3: Community Engagement consisting of one learning outcome requiring fifteen training hours per module. Module 4: Health Services consisting of eight items of learning outcomes totaling thirty training hours. The total number of training hours was 150. The suitability of the Social Entrepreneurship Competency-Based Curriculum in Elderly Care Business for Community Nurses was assessed by ten experts using the suitability assessment form developed by the researcher. By analyzing percentages, mean, and standard deviation, the assessment results showed that the overall curriculum was appropriate at the highest level ( = 4.78). When considering each item, it was found that all items were most suitable as well.